2023
DOI: 10.3390/jcm12083021
|View full text |Cite
|
Sign up to set email alerts
|

Transalbugineal Artificial Urinary Sphincter: A Refined Implantation Technique to Improve Surgical Outcomes

Abstract: The artificial urinary sphincter (AUS) implantation is an effective treatment of post-prostatectomy urinary incontinence (PPI). Still, it may result in troublesome complications such as intraoperative urethral lesion and postoperative erosion. Based on the multilayered structure of the tunica albuginea of the corpora cavernosa, we evaluated an alternative transalbugineal surgical technique of AUS cuff placement with the aim to decrease perioperative morbidity while preserving the integrity of the corpora caver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…-Social continence rate: defined as the use of no more than one pad per day [8]. -Unfavorable positive surgical margins: a single positive margin greater than or equal to 3 mm or a multifocal positive margin [9].…”
Section: Methodsmentioning
confidence: 99%
“…-Social continence rate: defined as the use of no more than one pad per day [8]. -Unfavorable positive surgical margins: a single positive margin greater than or equal to 3 mm or a multifocal positive margin [9].…”
Section: Methodsmentioning
confidence: 99%
“…Follow-up visits were performed at 3 and 6 months from surgery. A successful functional outcome was defined as achieving a cure (no pad use) or social continence (use of no more than one pad per day) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…40 While the majority of the authors use an extended AP in this setting, other authors reported similar results with a single-dose administration for both sling and artificial urinary sphincter in males. 108,109…”
Section: Therapeutic Proceduresmentioning
confidence: 99%